Lanthanide-centered luminescence evolution and potential anti-counterfeiting application of Tb3+/Eu3+ grafted melamine cyanurate hydrogen-bonded triazine frameworks. (8th January 2019) - Yang, Chaoqing; Kaczmarek, Anna M.; Folens, Karel; Du Laing, Gijs; Vrielinck, Henk; Khelifi, Samira; Li, Kai; Van Deun, Rik
Abstract : A novel type of Tb 3+ /Eu 3+ grafted melamine cyanurate hydrogen-bonded triazine framework phosphor (MCA:Ln) has been successfully obtained through an improved co-precipitation route. Abstract : A novel type of Tb 3+ /Eu 3+ grafted melamine cyanurate hydrogen-bonded triazine framework phosphor (MCA:Ln) has been successfully obtained through an improved co-precipitation route. The actual percentage of Ln 3+ ions is less than 1%. The obtained MCA:Ln phosphors show high thermo-stability (330 °C under air) and bright lanthanide (Ln)-centered photoluminescence. The Ln-centered luminescence evolution of MCA:Ln was systematically investigated by steady state excitation and emission spectra, fluorescence decay measurements, TG, XRD, and FT-Raman technology. Moreover, polyvinyl alcohol (PVA)–MCA:Ln mixtures demonstrated the potential to be used as colorful emission inks in the field of anti-counterfeiting.